Effect of ion irradiation on the properties multi-element plasma coatings - Eremin, E.N.; Syzdykova, A.S.; Guchenko, S.A.; Yurov, V.M.; Gyngazova, M.S. (IOP Conf. Series: Materials Science and Engineering, 2016)
The paper presents the results of the study of ion irradiation on the properties of multi-element plasma coatings. The coatings were bombarded by argon ions using heavy current ion source with a hollow cathode. After ion irradiation, the structure and physical properties of the coatings change, however, the nature of the changes is different for different coatings. To predict the behavior of the coating exposed to irradiation is virtually impossible. Therefore, structural studies and investigation of physical properties of the coatings to determine their functional characteristics are to be conducted.
Keywords: Effect; ion irradiation; properties multi-element; plasma coatings